Analysis of the role of the pyruvate decarboxylase gene family in Arabidopsis thaliana under low‐oxygen conditions. (10th April 2013) - Mithran, M.; Paparelli, E.; Novi, G.; Perata, P.; Loreti, E.; Whelan, J.
Abstract Plants under low‐oxygen conditions adapt their metabolism by inducing the fermentative pathway, with ethanol as the predominant end product. Activities of pyruvate decarboxylase (PDC) and alcohol dehydrogenase (ADH) are required for this pathway. While a single gene encodes ADH in Arabidopsis, a family of four genes codes PDC. The availability of microarray data sets enabled the relative importance of the four PDC genes under low oxygen to be assessed, and revealed that, contrary to previous published evidence, not only PDC1 but also PDC2 plays a role under hypoxic conditions. We observed a high level of expression, both at transcript and protein levels of PDCs, even under aerobic conditions when ADH is almost absent. This suggests that PDC has a role under aerobic conditions, which is not coupled to fermentative metabolism. The expression of both PDC1 and PDC2 is strongly up‐regulated under low oxygen. PDC1 is predominantly present in roots, while PDC2 appears to be leaf‐specific. We showed that mutations in both PDC1 and PDC2 result in lower tolerance to submergence.